Enhanced Light Trapping in Thin Film Solar Cells Using a Plasmonic Fishnet Structure - Sayan Seal; Vinay Budhraja; Liming Ji; Vasundara V. Varadan (International Journal of Photoenergy)
Incorporating plasmonic structures into the back spacer layer of thin film solar cells (TFSCs) is an efficient way to improve their performance. The fishnet structure is used to enhance light trapping. Unlike other previously suggested discrete plasmonic particles, the fishnet is an electrically connected wire mesh that does not result in light field localization, which leads to high absorption losses. The design was verified experimentally. A silver fishnet structure was fabricated using electron beam lithography (EBL) and thermal evaporation. The final fabricated structure optically resembles a TFSC. The results predicted by numerical simulations were reproduced experimentally on a fabricated sample. We show that light absorption in the a-Si absorber layer is enhanced by a factor of 10.6 at the design wavelength of 690 nm due to the presence of the fishnet structure. Furthermore, the total absorption over all wavelengths was increased by a factor of 3.2. The short-circuit current of the TFSC was increased by 30% as a result of including the fishnet.